Hyaluronate capsule and surface M protein in resistance to opsonization of group A streptococci. - Dale, J B (1996)
The major virulence determinant of group A streptococci is the ability to resist opsonization and phagocytic ingestion. The present studies were performed to compare the mechanisms of resistance to opsonization of type 18 and type 24 streptococci and to determine the relative roles of M protein-fibrinogen interaction and the hyaluronate capsule in preventing phagocytic ingestion and killing. By use of parent strains and acapsular transposon mutants in the presence and absence of fibrinogen, we show that type 18 and type 24 streptococci rely on somewhat different mechanisms for resistance to opsonization. Type 24 streptococci bound fibrinogen avidly to their surfaces, and encapsulated organisms were completely resistant to opsonization only in the presence of fibrinogen. In contrast, type 18 streptococci bound 10-fold less fibrinogen than type 24 streptococci and were fully resistant to phagocytosis only when they expressed capsule. The general structural characteristics of the amino-terminal halves of type 18 and type 24 M proteins differed in that type 18 M protein contained only one complete B repeat, whereas type 24 M protein contained five complete B repeats, a structural difference which could potentially be related to the differences in fibrinogen binding between the two serotypes. Immunofluorescence assays of complement deposition were used in combination with 125I-C3 binding assays to show that encapsulated type 24 streptococci were fully resistant to opsonization by C3 only in the presence of plasma. Encapsulated and unencapsulated type 18 streptococci were equally opsonized by C3 in either plasma or serum, yet only encapsulated organisms resisted phagocytic killing in blood. The results of this study indicate that opsonization by C3 does not necessarily lead to phagocytic ingestion and that the hyaluronate capsule and M proteins are variably important in resistance to different group A streptococci to opsonization and phagocytic killing.